Controlled drug delivery using layered double hydroxides - Senapati, Sudipta (My University, 2017)
This thesis entitled “Controlled drug delivery using layered double hydroxides” focuses on the design and development of layered double hydroxides based nanocarriers for delivery of anticancer drug and plasmid DNA vectors for cancer treatment. Chemotherapy has become an integral part of cancer treatment in recent years. Conventional chemotherapy is based on killing of cancer cells or inhibition of their growth and reproduction. However, during the process of killing of cancer cells, chemotherapeutic agents also damage healthy tissues, causing systemic toxicity and adverse side effects such as hair loss, loss of appetite, nausea, vomiting, anemia, fatigue, loss of taste buds, destruction of the immune system etc. It is therefore desirable to develop chemotherapeutics that can either passively or actively target cancerous cells to reduce the adverse side effects while improving therapeutic efficacy of anticancer agents. Nanocarriers can passively target cancer cells through enhanced permeation and retention (EPR) effect, prolong circulation time of the loaded therapeutics, enhanced bioavailability and minimize undesired toxic effects to healthy tissues. Layered double hydroxide (LDH) emerges recently as a promising two dimensional (2-D) nanocarrier due to its unique physical and chemical properties such as excellent anion exchange capacity, excellent biocompatibility, high drug loading efficacy, full protection of the loaded therapeutics, excellent endosome escape, stability in wider pH range, ease of preparation, low cost and biodegradability. LDHs consist of layers of a divalent metal cation Such as Mg2+, Zn2+, Ca2+, Ni2+, etc., with a trivalent metal cation isomorphically substituted to give the layers a net positive charge. This extra charge is counter balanced by interlayerhydrated exchangeable gallery anions, such as Cl−, NO3−, CO3 2− etc. Anionic therapeutic molecules (negatively charged drugs, genetic materials, peptides, proteins etc.) can easily be intercalated into the interlayer gallery, which provides full protection against enzymatic drug embedded polymer conjugate (PCL-RH). Cell adhesion behavior in PN-R is found to be superior as compared to pure polymer or even from pure LDH systems. Polymer nanoconjugate also exhibits better cellular uptake than that of pure drug and pure LDH. Sustained release of drug for prolonged period has been obtained in vivo system using albinorats showing healthy lever and other body parts using polymer nanohybrid against damaged lever using pure drug as evident from the histological observation, lever and renal functional tests. Thus, the developed polymer LDH nanoconjugate vehicle has been found to enhance the therapeutic efficacy of anti-cancer drug while reducing its adverse side effects.Li-Al based LDH has been synthesized for the delivery of plasmid gene into mammalian cancer cell. Li-Al based LDH demonstrates high loading capacity of DNA and can release the loaded DNA in a controlled manner. The developed gene delivery carrier has been found to provide remarkable protection against DNase I and also can protect the vector from thermal damage. This vehicle also demonstrated excellent cellular uptake performances. Successful gene transfection has been achieved by using the developed LDH based nanocarrier. Further, it is also found that the developed Li-Al LDH has efficiently induced GFP-p53 mediated apoptosis in HeLa cells to prove its efficacy.
Keywords: Hydroxides; Drug delivery